2014
DOI: 10.1093/brain/awu213
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal uptake of tau/pS422 antibody and reduced progression of tau pathology in a mouse model of Alzheimer‘s disease

Abstract: The severity of tau pathology in Alzheimer's disease brain correlates closely with disease progression. Tau immunotherapy has therefore been proposed as a new therapeutic approach to Alzheimer's disease and encouraging results have been obtained by active or passive immunization of tau transgenic mice. This work investigates the mechanism by which immunotherapy can impact tau pathology. We demonstrate the development of Alzheimer's disease-like tau pathology in a triple transgenic mouse model of Alzheimer's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 54 publications
6
145
0
1
Order By: Relevance
“…It has been shown that targeting the pS422 tau epitope with active vaccination decreases levels of insoluble phosphorylated tau and improves behavioral performance in transgenic mouse model of tauopathy [142]. Moreover, in a transgenic mouse model of AD, anti-tau pS422 antibodies are able to reduce accumulation of tau and induce its clearance via lysosomal pathways [88]. Anti-tau antibodies are internalized by neurons with tau aggregates via interaction with Fcγ receptors, and this internalization leads to the clearance of tau pathology in primary neurons [150], a mechanism that is probably shared with antibodies against α-syn (Fig.…”
Section: Immunotherapy Targeting Taumentioning
confidence: 99%
“…It has been shown that targeting the pS422 tau epitope with active vaccination decreases levels of insoluble phosphorylated tau and improves behavioral performance in transgenic mouse model of tauopathy [142]. Moreover, in a transgenic mouse model of AD, anti-tau pS422 antibodies are able to reduce accumulation of tau and induce its clearance via lysosomal pathways [88]. Anti-tau antibodies are internalized by neurons with tau aggregates via interaction with Fcγ receptors, and this internalization leads to the clearance of tau pathology in primary neurons [150], a mechanism that is probably shared with antibodies against α-syn (Fig.…”
Section: Immunotherapy Targeting Taumentioning
confidence: 99%
“…In Alzheimer disease, abnormal phosphorylation, misfolding and aggregation of tau lead to neurofibrillary tangle formation, and ultimately to neuronal cell death. 27 A proposed mode of action of the anti-tau/pS422 antibody Rb86 is that it binds to membrane-associated tau/pS422, upon which the antibody-antigen complexes are internalized and cleared within the cell, so that the neurodegenerative pathology of tau is ameliorated. An alignment of the VH and VL sequences of CD81K04, CD81K13 and Rb86 is given in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, passive immunization has also been investigated using a humanized monoclonal antibody targeting pS422 phospho-tau. In AD mice, chronic administration of this antibody reduced hyperphosphorylated tau accumulation [126], although clinical studies with this antibody were recently discontinued in phase 1 (see Table 1). …”
Section: Update On Dementiamentioning
confidence: 99%